STUDENTS' USE OF SOCIAL MEDIA: HOW IT EFFECT ON THE STUDENT TOLERANT CHARACTER AT MADRASAH? - M Risdamuddin; A. Malik; Miftahul Alimin; Inah Inah (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This study aims to determine the impact of the use of social media by students in madrasas on tolerant character. This research was conducted using a quantitative approach with a descriptive research method. The population of this study is madrasah students in Kebumen Regency. They were selected using the Simple Random Sampling method so that the number of samples taken was 75 students. Data was collected using a questionnaire distributed to respondents via GoogleForm. The results of the study showed that the intensity of social media use by students in madrasas was very high, namely 89%. This has a big impact on the tolerant character of students in madrasas, as evidenced by several aspects, including the content criteria that students see when using social media are in the high category with a percentage of 80%. In addition, student involvement in accessing content containing cultural or religious diversity values is very high with a percentage of 86%. Students’ interactions with individuals from different backgrounds when using social media are also very high with a percentage of 88%. The influence of social media on students' way of thinking about categorical differences is very high with a percentage of 92% and the use of social media as a means of learning about the importance of tolerance is very high with a percentage of 88%.